Maximum Bending Stress Analysis of Jute/Epoxy and Glass/Epoxy Polymer Composites - Md Said, Jamaliah; Jumahat, Aidah; Kushairi, Sahril; Shahrul Azhar, Ilya Izyan; Azlan, Nurul Faezah (International Journal of Integrated Engineering, 2022)
A surge in the use of fibre reinforced composites for biodegradable materials, which include both synthetic and natural fibres, to fulfil the strength requirements of composites while also being environmentally friendly has resulted in the use of these materials becoming increasingly popular. Researchers have been working to improve natural fibre qualities to partially replace synthetic fibre, even though not entirely. The research can be accomplished by modelling and simulation techniques, which are becoming more prevalent as technology advances. The approaches have the benefits of being efficient in addressing any material model, boundary conditions, and complicated form structure that may be encountered. This study uses ANSYS APDL, a finite element analysis tool, to carry out flexural test. These factors, as well as the fibre ply orientation, lay-up sequence, and fibre volume percentage, have an impact on the maximum stress of each composite, which are investigated in this study. In the lay-up sequence of [(+?, -?)2] s, with fibre ply orientation of 0? the maximum flexural stress obtains for glass/epoxy (vf=60 %), glass epoxy (vf=30 %), and jute/epoxy (vf=30 %) is 214.64 MPa, 153.77 MPa, and 82.91 MPa and for fibre ply orientation of 90? the maximum bending stress is 55.41 MPa, 18.39 MPa and 8.37 MPa respectively. Furthermore, the impact of off-axis plies in the 0° fibre ply orientation can be observed in the maximum bending stress of the [?4,04] s lay-up sequence, which is a function of the number of off-axis plies in the 0° fibre ply orientation. When using the lay-up sequence [904,04] s, the maximum flexural stress for glass/epoxy (vf=60 percent), glass/epoxy (vf=30 percent), and jute/epoxy (vf=30 percent) is 83.39 MPa, 23.04 MPa, and 17.92 MPa, respectively. When bending tests are performed, the 0° fibre ply orientation produces the highest maximum stress, followed by 45° and 90°. When comparing 0° plies composites with off-axis angles to plies composites, the lay-up sequence of 0° plies with off-axis angles exhibits the highest maximum stress.